Coronary Revascularization of Giant Aneurysms in Children With Kawasaki Disease: A Report of Two Cases - Akimoto, Katsumi; Harada, Mana; Oda, Hisayuki; Furukawa, Takeshi; Takahashi, Ken; Kishiro, Masahiko; Shimizu, Toshiaki; Nakanishi, Keisuke; Kawasaki, Shiori; Amano, Atsushi (Frontiers in Pediatrics, 2020)
In recent years, >100 cases of coronary artery stenotic lesions due to Kawasaki disease were treated with coronary artery bypass grafting (CABG). Surgical indications include stenosis of >75%, myocardial infarction history, electrocardiographic changes, and ischemia, as detected by myocardial scintigraphy and electrocardiography, due to drugs or exercise. Some centers have reported good patency rates, even in infants. The advantages of CABG in younger patients are minimal loss of left ventricular function, early elimination of post-operative ischemia risk, and improved quality of life. However, the disadvantage of performing CABG in younger patients is the small coronary artery diameter and the thin vessel wall, which can lead to post-operative occlusion, especially when performed by inexperienced surgeons. The optimal timing of CABG varies by institution and case, which depends on the presence or absence of complications, such as left ventricular dysfunction or valve regurgitation, and surgeon's experience. Importantly, unlike adult surgery, childhood CABG needs to be kept open for the very longest possible period of time to determine the optimal conditions for surgery. We report two pediatric cases of giant coronary artery aneurysms diagnosed in infancy. During school age, the patients had a mild decline of left ventricular ejection function. In one case, there were no clinical symptoms because of the development of collateral vessels and limitation of exercise. Both patients underwent surgery with good results. The gastric gastroepiploic artery could be anastomosed owing to the development of collateral blood vessels, although it was obstructed. At 1 year after surgery, both patients had a good post-operative course without complications of anastomotic stenosis or myocardial damage due to aneurysm resection. If conditions are favorable, bypass surgery can be postponed to several years until the coronary arteries are sufficiently large to warrant a delay in coronary artery stenosis in cases of infantile Kawasaki disease.